Indium-bearing sulfides from the Hämmerlein skarn deposit, Erzgebirge, Germany: evidence for late-stage diffusion of indium into sphalerite - Bauer, Matthias E.; Seifert, Thomas; Burisch, Mathias; Krause, Joachim; Richter, Nancy; Gutzmer, Jens (Mineralium deposita, 2019)
At the Hämmerlein skarn deposit, located in the western Erzgebirge (Germany), a major cassiterite-dominated Sn mineralization stage is spatially associated with a younger Zn-Cu-In sulfide mineralization stage. In this contribution, we provide the first detailed description of the Zn-Cu-In sulfide mineralization stage, based on field geological observations combined with detailed petrographic studies and electron probe microanalysis data. Indium-rich sulfide mineralization occurs as irregular, semi-massive lenses or as infill of short, discontinuous veinlets that crosscut the cassiterite-bearing skarn assemblage. Indium- and Cu-rich sphalerite and roquesite are found to be closely associated with In-bearing chalcopyrite. The highest In concentrations in sphalerite occur at the rims and along cracks of sphalerite grains. The distribution resembles diffusion profiles, suggesting that the In enrichment is due to an hydrothermal overprint that postdates the initial formation of both sphalerite and chalcopyrite. Textural relations illustrate that the diffusion fronts in sphalerite grains are thicker where they are in contact to anhedral masses of hematite and magnetite. Our observations suggest that In enrichment in sphalerite at the Hämmerlein skarn deposit is due to the decomposition of In-bearing chalcopyrite. The resultant release of Fe led to the formation of hematite and magnetite, whereas Cu and In were incorporated into sphalerite along grain boundaries and micro fractures. Incorporation into the sphalerite lattice took place by coupled substitution of Cu + + In 3+ ↔ 2Zn 2+ , suggesting that the concurrent availability of Cu and In may be an essential factor to enrich In in sphalerite in hydrothermal ore-forming environments.